Use of microsensor platform to differentiate metabolic parameters associated with developmental timing and sex of individual bovine blastocysts - Ming-Hao Cheng; Kyle J. Fresa; Raul A. Gonzalez-Castro; Adam J. Chicco; Elaine M. Carnevale; Thomas W. Chen (Theriogenology, 2026)

AI-driven forest restoration: A governance framework for people and nature - Fernando Morales-Rueda; Maganizo Kruger Nyasulu; Harry W. Fischer; Ingo Fetzer; Siham Tabik; Domingo Alcaraz-Segura; Jorge Castro (Environmental Science & Policy, 2026)

Evaluation of water quality from tubular wells in Brazil - G. G. O. de Souza; J. W. G. Castro; R. S. da Cadorso; E. M. de Lima; J. F. L. de Pereira; M. P. da Silva; Y. T. C. da Santos; F. G. Rodriguês; J. G. M. da Costa; H. D. M. Coutinho; G. B. Brito (International Journal of Energy and Water Resources, 2026)

Seasonal Variability of Residence Time and Ocean Exchange in a Semi-enclosed Gulf in Northwestern Australia - Camille M. Grimaldi; Michael V. W. Cuttler; Johan Reyns; Jessica A. Benthuysen; Carolina Castro-Sanguino; Luke Thomas; James P. Gilmour; Ryan J. Lowe (Estuaries and Coasts, 2026)
Coastal water exchange with the open ocean plays a key role in regulating the transport and distribution of nutrients, heat, pollutants, suspended sediments and organisms in semi-enclosed systems. In this study, we quantify coastal water exchange for Exmouth Gulf (Australian North West Shelf), a globally significant water body adjacent to the Ningaloo Coast World Heritage Area. We use a high-resolution (200 m) hydrodynamic model, along with particle tracking, to quantify the spatiotemporal variation in circulation, water residence times, and export from the Gulf to the adjacent ocean. Water residence times in Exmouth Gulf are primarily influenced by tidal and wind forcing, with wind waves providing an additional, though secondary, contribution. The shortest Gulf residence times occurred in spring (∼52 days) and the longest in winter (∼276 days). Spatially (and across seasons), residence times within specific subregions were shortest near the western entrance (< 1 day), and longest in the southern Gulf (> 49 days). Export to the ocean was strongest during winter (albeit relatively small, accounting for only 5% of all particles), whereas during the rest of the year particles predominantly remained along the wide, shallow continental shelf to the north-east of the Gulf. Connections between the Gulf and the Ningaloo Coast World Heritage Area varied seasonally in strength, reflecting changes in the regional circulation drivers. Overall, the seasonality of regional wind patterns (via surface currents and wind waves) shaped the residence time and export of material and organisms to surrounding areas. We show that wind waves reduce residence times by up to 15% in parts of the Gulf and thus are an important component of system modelling. A thorough understanding of such dynamics is critical to make informed decisions about the conservation and management of the area.

On-Demand Hospital Manufacturing of Baclofen Lozenges Using Pharmaceutical 3D Printing - Daniel Grandal-Gonzalez; Carlos Bendicho-Lavilla; Eduardo Diaz-Torres; Rocio Sanin-Fontela; María L. Couce; María José de Castro-López; Isabel Gonzalez-Alvarez; Marta Gonzalez-Alvarez; Alejandro Ruiz-Picazo; Marival Bermejo; Pedro Garcia-Salom; Abdul W. Basit; et al. (Pharmaceutical Research, 2026)
Purpose Dysphagia in neurological patients complicates oral drug administration. Manual preparation of lozenges/troches lacks precision and scalability. This study investigates the feasibility of implementing a pharmaceutical 3D printer in a hospital pharmacy for the automated production of personalized baclofen troches. Methods Baclofen troches were manufactured in a hospital pharmacy setting, both manually and via pharmaceutical 3D printer. Quality was evaluated using Process Analytical Technologies (PAT). Performance was assessed through European Pharmacopoeia (EP) tests for drug content, mass uniformity, in vitr o dissolution, disintegration, and a six-month stability study. Results Printed troches complied with all EP acceptance criteria for drug content and mass uniformity, whereas manual formulations failed, particularly at the lowest dose. Printed troches demonstrated immediate drug release, consistent quality across batches, and remained stable for six months. 3D printing showed superior precision over traditional manual compounding. Conclusions This research describes the first successful implementation of an automated blister-filling workflow using a pharmaceutical 3D printer within a hospital pharmacy setting, spanning from manufacturing and dispensing to direct patient administration. The automated approach provides a significant advancement in personalized medicine, ensuring safer, more accurate, and efficient treatment options for patients with specific needs like dysphagia.

Medicinal plant discrimination in Paramos and cloud forests of northern Peru: A study of deep learning techniques and a novel approach for data augmentation - W. Castro; M. Juarez; D. Gálvez-Paucar; V. Tirado; J. Gonzáles; F. Torres-Guevara (Remote Sensing Applications: Society and Environment, 2026)

Effect of sodium bicarbonate on performance and markers of kidney and gastrointestinal injury during repeated sprints in the heat - Jonathan W. Specht; Marissa Ramirez; Jennifer Raef; Mackenzie Schwartz; Alyssa R. Bailly; Oscar Chavez; Ozan Kumbasar; Jade X. Dawson; Jessica Apodaca; Raul Freire; Whitley C. Atkins; Flávio de Castro Magalhães; et al. (European Journal of Applied Physiology, 2026)
Purpose We tested the hypotheses that sodium bicarbonate (SB) supplementation improves performance, reduces markers of acute kidney injury (AKI) risk, and increases markers of acute gastrointestinal injury (AGI) during repeated sprints in the heat. Methods Using a double-blind design, 10 recreationally endurance-trained participants ingested 0.2 g/kg of body weight of SB or placebo before cycling in the heat (dry-bulb: 40 °C, relative humidity: 20%). Exercise bouts included a 22-min warm-up, then 4-sets of 5 × 6-sec maximal-effort standing cycling sprints. Core temperature (Tc) was measured at baseline, end of warm-up, after set two of sprints, and post-exercise bouts. Urine and plasma collected pre-ingestion and pre-, post-, and 1-h post-exercise were analyzed for markers of AKI risk, AGI, and endotoxemia. Results SB increased peak (average difference between conditions: 21 ± 11 W, condition effect: p = 0.02) and average ( p = 0.03) power across the sprints. Tc increased from pre- to post-exercise (placebo: Δ1.3 ± 0.3 °C, SB: Δ1.4 ± 0.4 °C, time effect: p < 0.001), but there were no effects of condition or interaction. Exercise increased the primary marker of AKI (urinary IGFBP7×TIMP-2, time effect: p = 0.005) but not urinary NGAL. There were no condition or interaction effects for either AKI marker. Plasma I-FABP, a marker of AGI, increased post-exercise bouts (placebo: Δ291 ± 550 pg/mL, SB: Δ397 ± 482 pg/mL, p = 0.03), with no condition or interaction effects. There were no significant effects for markers of endotoxemia (LBP, sCD14). Conclusions SB supplementation improves repeat sprint performance in the heat without altering Tc, markers of AKI risk, or markers of AGI.

Efficacy of cold plasma and pulsed UV-light against Salmonella and E. coli O157:H7 on fresh basil leaves - Edson Douglas Silva Pontes; Donald W. Schaffner; Raquel Taynan Cunha Vieira; Emilio de Castro Miguel; Geany Targino de Souza Pedrosa; Fabiano André Narciso Fernandes; Sueli Rodrigues; Marciane Magnani (Food Microbiology, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Apple damages classification: Using the best convolutional neural network to discard low surface quality fruit in packing plants - Martín Molina; Julio Godoy; John W. Castro; Vladimir Riffo (Computers and Electronics in Agriculture, 2026)

Influence of almond’s canopy-induced shadows on actual evapotranspiration estimation by the TSEB model using sUAS multispectral and thermal imagery - M. R. Duran-Gomez; A. Torres-Rua; L. Hipps; W. Kustas; N. E. Bambach; K. Knipper; I. Wright; A. J. McElrone; J. H. Prueger; J. G. Alfieri; C. Coopmans; K. Meza; et al. (Irrigation Science, 2026)
Over the past decade, the estimation of water requirements in almond orchards has improved through the application of remote sensing models like the Two-Source Energy Balance (TSEB) model using various remote sensing platforms. However, there is limited understanding of how canopy-induced shadows influence surface reflectance and thermal infrared (TIR) signals particularly from small Unmanned Aircraft System (sUAS) imagery in energy balance models, and the effect on Latent Heat Flux (LE) estimations. This study evaluates LE estimates from the Priestley-Taylor TSEB model (TSEB-PT) with and without shadow filtering using sUAS-based multispectral and TIR imagery. It establishes a baseline for the impact of shadow filtering on model inputs and performance. Datasets were collected in 2021 and 2022, as part of the USDA led Tree-crop Remote sensing of Evapotranspiration eXperiment (T-REX) in almonds orchards across California. LAI-2200 C Plant Canopy Analyzer measurements facilitated the calibration of an empirical Leaf Area Index (LAI) model based on canopy fractional cover (FC) and NDVI (R 2 = 0.68). Shadow filtering caused land surface temperature (LST) differences up to 5 °C in young to semi-mature orchards (FC 0.40–0.80). In contrast, mature orchards (FC > 0.80) showed minimal influence due to the limited shadow occurrence on the imagery. Shadows appeared to reduce surface albedo (α alb ), mainly in interrow areas, thereby affecting the absorption of radiation and the partitioning of energy balance components. Their presence in sUAS imagery also hindered canopy delineation, impacting the accuracy of key TSEB inputs derived from canopy physical characteristics. Thus, the influence of shadow on TSEB estimated LE was more significant in lower fractional tree covers. While LE estimated by TSEB-PT without shadow filtering showed better agreement with observations, combining instantaneous TIR imagery with solar-noon shortwave data is recommended for accurate ETa assessment using sUAS datasets. These baseline results can be improved with more advanced formulations, supporting continued research on E/T partitioning and water stress in almond orchards under varying environmental conditions, particularly when there is advection of hot dry air.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Thermodynamic model and infrared thermography monitoring system for convective drying of goldenberry (Physalis peruviana) - T. Chuquizuta; W. Castro; M. Castro-Giraldez; P.J. Fito (Journal of Food Engineering, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

The ornithine-arginine cycle supported a toxic, metalimnic Planktothrix rubescens bloom - Brittany N. Zepernick; David J. Niknejad; Emily E. Chase; Blessing A. Abiodun; Meaghan J. Adler; Katelyn A. Houghton; Jason L. Olavesen; Qudus Sarumi; Alexander R. Truchon; Jillian L. Walton; Jack H. Cheshire; Keara Stanislawczyk; et al. (Harmful Algae, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Mangrove blue carbon in Laguna de Términos, México, a protected area: Spatial variability, sources and factors related - Jorge A. Herrera-Silveira; Mónica Pech-Cárdenas; Siuling G. Cinco-Castro; Eunice Pech-Poot; Flor Árcega-Cabrera; Raquel Iturria-Dawn; Andrés Canul-Cabrera; Juan E. Mendoza-Martínez; Azucena Dótor-Almazán; John W. Day; Steven W.J. Canty; Miguel Cifuentes-Jara; et al. (Regional Studies in Marine Science, 2025)

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

Transcriptomic resilience to heat stress in a wide-spread Acropora coral - Declan J. A. Stick; W. Jason Kennington; Carolina Castro-Sanguino; Shannon L. Duffy; Dean Z. Tysdale; James P. Gilmour; Luke Thomas (Coral Reefs, 2025)
As climate change progresses and severe disturbances become routine, understanding rates and mechanisms of recovery in habitat-forming species is central to predicting the broader response of ecosystems to climate change. Here, we combined acute experimental heat stress and RNA sequencing to explore patterns of transcriptome plasticity and resilience to heat stress in a common Acropora coral from the World Heritage-listed Ningaloo Reef. Our data showed that corals subjected to sub-bleaching temperatures (33 ℃) elicited a large transcriptional response during heat stress, but quickly recovered to baseline levels of expression 16 h after temperatures returned to pre-treatment conditions, with no evidence of bleaching. In contrast, corals exposed to a one degree increase (34 ℃) from the sub-bleaching heat treatment, mounted a transcriptional response nearly twice that of the sub-bleaching temperature, showed a lingering stress response in their transcriptome, and eventually bleached. Moreover, variation in the severity of bleaching among colonies was linked to patterns of transcriptome recovery—individuals that bleached heavily showed a larger lag in transcriptional recovery than those with lower levels of bleaching. Together, these findings provide new insight into the genetic mechanisms of heat stress recovery in coral and highlight the role of transcriptional plasticity in the resilience of coral to increasing disturbances.

Conservation for production? The benefits of mangroves for sustainable shrimp aquaculture - Aji W. Anggoro; Miguel Castro; Muhammad Ilman; Sara Leavitt; Basir; Mariski Nirwan; Vabian Adriano; Andi Trisnawati; Topik Hidayat; Rahmadi Muis; Dzimar A. R. Prakoso; Yusuf Fajariyanto; et al. (Aquaculture International, 2025)

Brazilian Cerrado soil microbiota captures the impacts of agricultural practices and unveils a promising ecosystem for antimicrobial peptide discovery - F.T.P.K. Távora; R.S. Oliveira; T.B. Rios; D.G. Ribeiro; L.M. Souza; F.B. Reis Junior; W. Fontes; M.S. Castro; M.V. Sousa; O.L. Franco; A. Mehta (Applied Soil Ecology, 2025)

Non-invasive monitoring of goldenberry freezing using infrared thermography and radiofrequency dielectric spectroscopy - T. Chuquizuta; W. Castro; M. Castro-Giraldez; P.J. Fito (Innovative Food Science & Emerging Technologies, 2025)

Panta Rhei: a decade of progress in research on change in hydrology and society - Heidi Kreibich; Murugesu Sivapalan; Amir AghaKouchak; Nans Addor; Hafzullah Aksoy; Berit Arheimer; Karsten Arnbjerg-Nielsen; Cynthia Vail-Castro; Christophe Cudennec; Mariana Madruga de Brito; Giuliano Di Baldassarre; David C. Finger; et al. (Hydrological Sciences Journal, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Valorization of residual ashes from boiler combustion process into activated carbon for adsorption of food industry wastewater - L. E. N. Castro; L. R. Matheus; W. G. Sganzerla; L. M. S. Colpini (International Journal of Environmental Science and Technology, 2025)

Early Aptian development and OAE 1a-linked demise of a carbonate platform in the western Tethys: Lower Cretaceous of Sierra Mariola (South Iberian Paleomargin, SE Spain) - Rafael Martínez-Rodríguez; José M. Castro; Ginés A. de Gea; Luis M. Nieto; Pedro A. Ruiz-Ortiz; Peter W. Skelton (Cretaceous Research, 2025)

Evaluating the suitability of large-scale datasets to estimate nitrogen loads and yields across different spatial scales - Andrés Felipe Suárez-Castro; Dale M. Robertson; Bernhard Lehner; Marcelo L. de Souza; Michael Kittridge; David A. Saad; Simon Linke; Rich W. McDowell; Mohammad Hassan Ranjbar; Olivier Ausseil; David P. Hamilton (Water Research, 2025)

Evaluating the precise grapevine water stress detection using unmanned aerial vehicles and evapotranspiration-based metrics - V. Burchard-Levine; I. Borra-Serrano; J. M. Peña; W. P. Kustas; J. G. Guerra; J. Dorado; G. Mesías-Ruiz; M. Herrezuelo; B. Mary; L. M. McKee; A. I. de Castro; S. Sanchez-Élez; et al. (Irrigation Science, 2025)
Precise irrigation management requires accurate knowledge of crop water demand to adequately optimize water use efficiency, especially relevant in arid and semi-arid regions. While unoccupied aerial vehicles (UAV) have shown great promise to improve the water management for crops such as vineyards, there still remains large uncertainties to accurately quantify vegetation water requirements, especially through physically-based methods. Notably, thermal remote sensing has been shown to be a promising tool to evaluate water stress at different scales, most commonly through the Crop Water Stress Index (CWSI). This work aimed to evaluate the potential of a UAV payload to estimate evapotranspiration (ET) and alternative ET-based crop water stress indices to better monitor and detect irrigation requirements in vineyards. As a case study, three irrigation treatments within a vineyard were implemented to impose weekly crop coefficient (Kc) of 0.2 (extreme deficit irrigation), 0.4 (typical deficit irrigation) and 0.8 (over-irrigated) of reference ET. Both the original Priestley-Taylor initialized two-source energy balance model (TSEB-PT) and the dual temperature TSEB (TSEB-2T), which takes advantage of high-resolution imagery to discriminate canopy and soil temperatures, were implemented to estimate ET. In a first step, both ET models were evaluated at the footprint level using an eddy covariance (EC) tower, with modelled fluxes comparing well against the EC measurements. Secondly, in-situ physiological measurements at vine level, such as stomatal conductance (g st ), leaf (Ψ leaf ) and stem (Ψ stem ) water potential, were collected simultaneously to UAV overpasses as plant proxies of water stress. Different variants of the CWSI and alternative metrics that take advantage of the partitioned ET from TSEB, such as Crop Transpiration Stress Index (CTSI) and the Crop Stomatal Stress Index (CSSI), were also evaluated to test their statistical relationship against these in-situ physiological indicators using the Spearman correlation coefficient ( ρ ). Both TSEB-PT and TSEB-2T CWSI related similarly to in-situ measurements (Ψ leaf : ρ ~ 0.4; Ψ stem : ρ ~ 0.55). On the other hand, stress indicators using canopy fluxes (i.e. CTSI and CSSI) were much more effective when using TSEB-2 T (Ψ leaf : ρ = 0.45; Ψ stem : ρ = 0.62) compared to TSEB-PT (Ψ leaf : ρ = 0.18; Ψ stem : ρ = 0.49), revealing important differences in the ET partitioning between model variants. These results demonstrate the utility of physically-based models to estimate ET and partitioned canopy fluxes, which can enhance the detection of vine water stress and quantitatively assess vine water demand to better manage irrigation practices.

Evaluation of impacts of biosolids application and drainage water management on soil N2O and CH4 emissions using the flux gradient method - Qiurui Zhu; Eric A. Davidson; Jacob G. Hagedorn; Mark S. Castro; Thomas R. Fisher; Rebecca J. Fox; Shannon E. Brown; James W. Lewis (Agriculture, Ecosystems & Environment, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Testing molecular date estimates using an ecological and vicariant case study in treefrogs: The Geological‐Ecological Molecular Calibration - Michael J. Jowers; Jesús Muñoz Pajares; John Weber; Jeanette Arkle; Salvador Arenas‐Castro; Simon Y. W. Ho; Gilson A. Rivas; John C. Murphy; Amaël Borzée; R. Alexander Pyron; Marcos Perez‐Losada; Mayke De Freitas; et al. (Journal of Biogeography, 2024)
Aim To date a vicariant event through the mutualistic relationship of a hylid frog and its bromeliad host found across two isolated mountain ranges as part of an island–continental split and to use this information to calibrate a molecular dating analysis of hylids. Location South America. Time Period Pliocene. Major Taxa Studied Treefrogs, Arboranae. Methods Pliocene tectonic movements sank a portion of a mountain range that connected present‐day Trinidad (island) and northern Venezuela, eventually isolating populations of the golden tree frog Phytotriades auratus and its host bromeliad Glomeropitcairnia erectiflora on both sides of a saltwater barrier. We estimated the submersion rate timing of the vicariant event, then employed ecological niche modelling to establish the distribution of the frog and its host to the Pliocene. We generated nucleotide sequence data for the hylid on each side of the marine barrier and proposed a biogeographic calibration for the split between populations. Using Bayesian phylogenetic analysis, we evaluated the impact of incorporating this biogeographic calibration on estimates of treefrog divergence times. Results A relatively continuous, high‐elevation mountain range existed before the Pliocene and the opening of the Gulf of Paria (4.45 ± 0.85 Ma). Phytotriades auratus and G. erectiflora would have been distributed across the Paria and Northern Range mountains as a single population since the Pliocene. Divergence times among treefrogs (Arboranae) were older than those inferred using fossil calibrations alone, with mean age estimates for subfamilies and genera being ~2 and ~1.2 million years older, respectively. Main Conclusions Our study presents a biogeographic calibration based on a vicariant model that connects the evolution of the populations of a hylid through geology and ecological data. The implementation of this date as a molecular clock calibration reduces the uncertainty in date estimates for the shallower nodes in the phylogeny of Arboranae.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Aging- and alcohol-associated spatial transcriptomic signature in mouse acute pancreatitis reveals heterogeneity of inflammation and potential pathogenic factors - Rachel R. Tindall; Yuntao Yang; Isabella Hernandez; Amy Qin; Jiajing Li; Yinjie Zhang; Thomas H. Gomez; Mamoun Younes; Qiang Shen; Jennifer M. Bailey-Lundberg; Zhongming Zhao; Daniel Kraushaar; et al. (Journal of Molecular Medicine, 2024)
The rapidly aging population is consuming more alcohol, leading to increased alcohol-associated acute pancreatitis (AAP) with high mortality. However, the mechanisms remain undefined, and currently there are no effective therapies available. This study aims to elucidate aging- and alcohol-associated spatial transcriptomic signature by establishing an aging AAP mouse model and applying Visium spatial transcriptomics for understanding of the mechanisms in the context of the pancreatic tissue. Upon alcohol diet feeding and caerulein treatment, aging mice (18 months) developed significantly more severe AAP with 5.0-fold increase of injury score and 2.4-fold increase of amylase compared to young mice (3 months). Via Visium spatial transcriptomics, eight distinct tissue clusters were revealed from aggregated transcriptomes of aging and young AAP mice: five acinar, two stromal, and one islet, which were then merged into three clusters: acinar, stromal, and islet for the comparative analysis. Compared to young AAP mice, > 1300 differentially expressed genes (DEGs) and approximately 3000 differentially regulated pathways were identified in aging AAP mice. The top five DEGs upregulated in aging AAP mice include Mmp8 , Ppbp , Serpina3m , Cxcl13 , and Hamp with heterogeneous distributions among the clusters. Taken together, this study demonstrates spatial heterogeneity of inflammatory processes in aging AAP mice, offering novel insights into the mechanisms and potential drivers for AAP development. Key messages Mechanisms regarding high mortality of AAP in aging remain undefined. An aging AAP mouse model was developed recapturing clinical exhibition in humans. Spatial transcriptomics identified contrasted DEGs in aging vs. young AAP mice. Top five DEGs were Mmp8 , Ppbp , Serpina3m , Cxcl13 , and Hamp in aging vs. young AAP mice. Our findings shed insights for identification of molecular drivers in aging AAP.

Australian non-perennial rivers: Global lessons and research opportunities - Margaret Shanafield; Melanie Blanchette; Edoardo Daly; Naomi Wells; Ryan M. Burrows; Kathryn Korbel; Gabriel C. Rau; Sarah Bourke; Gresley Wakelin-King; Aleicia Holland; Timothy Ralph; Gavan McGrath; et al. (Journal of Hydrology, 2024)

Workflow to facilitate the detection of new psychoactive substances and drugs of abuse in influent urban wastewater - Richard Bade; Denice van Herwerden; Nikolaos Rousis; Sangeet Adhikari; Darren Allen; Christine Baduel; Lubertus Bijlsma; Tim Boogaerts; Dan Burgard; Andrew Chappell; Erin M. Driver; Fernando Fabriz Sodre; et al. (Journal of Hazardous Materials, 2024)

Resilience of Ricinus communis L. to high temperatures during germination and seedling growth resulting from efficient superoxide dismutase modulation - Valdir G. Neto; Wilco Ligterink; Henk W. M. Hilhorst; Isabela D. Santos; Carine R. Teixeira; Emily E. Santos; Marta B. Loureiro; Daniele Takahashi; Luzimar G. Fernandez; Paulo R. Ribeiro; Renato D. De Castro (Brazilian Journal of Botany, 2024)

What makes a cyanobacterial bloom disappear? A review of the abiotic and biotic cyanobacterial bloom loss factors - Ted D. Harris; Kaitlin L. Reinl; Marzi Azarderakhsh; Stella A. Berger; Manuel Castro Berman; Mina Bizic; Ruchi Bhattacharya; Sarah H. Burnet; Jacob A. Cianci-Gaskill; Lisette N. de Senerpont Domis; Inge Elfferich; K. Ali Ger; et al. (Harmful Algae, 2024)

Valorization of black grape pomace by pressurized hot water extraction and hydrolysis: Real-time online and in-line monitoring - Francisco W. Maciel-Silva; Luiz E.N. Castro; William Gustavo Sganzerla; Josiel Martins Costa; Mauricio A. Rostagno; Tânia Forster-Carneiro (Journal of Environmental Chemical Engineering, 2024)

Enzymatic de-esterification and depolymerization of apple pomace (Malus domestica var. Blanca de Asturias) pectin impacts lipid digestion in vitro - B.E. Morales-Contreras; L. Wicker; W. Rosas-Flores; J.A. Gallegos-Infante; J.C. Contreras-Esquivel; J. Morales-Castro (Food Hydrocolloids, 2024)

Adaptation of sea turtles to climate warming: Will phenological responses be sufficient to counteract changes in reproductive output? - M. M. P. B. Fuentes; A. J. B. Santos; A. Abreu‐Grobois; R. Briseño‐Dueñas; J. Al‐Khayat; S. Hamza; S. Saliba; D. Anderson; K. W. Rusenko; N. J. Mitchell; M. Gammon; B. P. Bentley; et al. (Global Change Biology, 2024)
Sea turtles are vulnerable to climate change since their reproductive output is influenced by incubating temperatures, with warmer temperatures causing lower hatching success and increased feminization of embryos. Their ability to cope with projected increases in ambient temperatures will depend on their capacity to adapt to shifts in climatic regimes. Here, we assessed the extent to which phenological shifts could mitigate impacts from increases in ambient temperatures (from 1.5 to 3°C in air temperatures and from 1.4 to 2.3°C in sea surface temperatures by 2100 at our sites) on four species of sea turtles, under a “middle of the road” scenario (SSP2‐4.5). Sand temperatures at sea turtle nesting sites are projected to increase from 0.58 to 4.17°C by 2100 and expected shifts in nesting of 26–43 days earlier will not be sufficient to maintain current incubation temperatures at 7 (29%) of our sites, hatching success rates at 10 (42%) of our sites, with current trends in hatchling sex ratio being able to be maintained at half of the sites. We also calculated the phenological shifts that would be required (both backward for an earlier shift in nesting and forward for a later shift) to keep up with present‐day incubation temperatures, hatching success rates, and sex ratios. The required shifts backward in nesting for incubation temperatures ranged from −20 to −191 days, whereas the required shifts forward ranged from +54 to +180 days. However, for half of the sites, no matter the shift the median incubation temperature will always be warmer than the 75th percentile of current ranges. Given that phenological shifts will not be able to ameliorate predicted changes in temperature, hatching success and sex ratio at most sites, turtles may need to use other adaptive responses and/or there is the need to enhance sea turtle resilience to climate warming.

Quantification of soil N2O and CH4 fluxes using the flux gradient method on a drainage water managed farm on the eastern shore of Maryland - Qiurui Zhu; Eric A. Davidson; Jacob G. Hagedorn; Mark S. Castro; Thomas R. Fisher; Rebecca J. Fox; Shannon E. Brown; James W. Lewis (Agricultural and Forest Meteorology, 2023)

Sulfolipid substitution ratios of Microcystis aeruginosa and planktonic communities as an indicator of phosphorus limitation in Lake Erie - Robbie M. Martin; Maddie K. Denney; Helena L. Pound; Justin D. Chaffin; George S. Bullerjahn; R. Michael L. McKay; Arthur Zastepa; Katarina A. Jones; Hector F. Castro; Shawn R. Campagna; Steven W. Wilhelm (Limnology and Oceanography, 2023)
Phosphorus (P) availability frequently limits primary production in lakes, influences the physiology of phytoplankton, shapes community structure, and can stimulate or constrain the formation of cyanobacterial blooms. Given the importance of P, numerous methods are available to assess P stress in phytoplankton communities. Marine phytoplankton are known to substitute sulfolipids for phospholipids in response to P limitation. We asked whether sulfolipid substitution might serve as an additional indicator of P stress in freshwater phytoplankton communities. The question was addressed using cultures of Microcystis aeruginosa , Lake Erie microcosms, and surveys of lipid profiles in Lake Erie during a Microcystis spp. bloom. Peak area response ratios of the intact polar lipids sulfoquinovosyldiacylglycerol (SQDG) to phosphatidylglycerol (PG) were used as the metric of lipid substitution. In cultures of M. aeruginosa NIES‐843, the SQDG : PG ratio increased from ~ 0.9 to ~ 3.3 with decreasing P concentration. In P‐limited communities, the SQDG : PG ratio increased from ~ 6 to ~ 11 after 48 h in microcosm controls, while P amendments reduced the ratio to ~ 3. In Lake Erie surveys, the SQDG : PG ratio ranged from ~ 0.4 to ~ 7.4 and was negatively correlated (Pearson r = −0.62) with total dissolved P. The SQDG : PG ratio was not correlated with concentrations of chlorophyll a , soluble reactive P, or N : P molar ratios. These results demonstrated that M. aeruginosa and Microcystis ‐dominated communities remodel lipid profiles in response to P scarcity, providing a potential short‐term, time‐integrated biomarker of nutrient history and P stress in fresh waters.

Progradation of a shallow carbonate platform developed on a fault-block in the Western Tethys (lower Aptian, Sierra de Bedmar-Jódar, Prebetic of Jaén, Spain) - Rafael Martínez-Rodríguez; Luis M. Nieto; José M. Castro; Ginés A. de Gea; Pedro A. Ruiz-Ortiz; José M. Molina; Peter W. Skelton (Facies, 2023)
The Middle Member of the Llopis Fm in the Sierra de Bedmar-Jódar Unit of the Prebetic Zone of Jaén (southern Spain) was deposited on a shallow-marine platform of the Southern Iberian Continental Margin during the earliest Aptian. Detailed field logging of nine stratigraphic sections and facies mapping have allowed seven lithofacies associations (L1–L6) to be distinguished, one siliciclastic (L1) and five carbonate facies (L2–6). The succession is composed of eight consecutive elemental sequences of lithofacies associations L1–L6. Each elemental sequence is interpreted as representing one episode of shallowing-upwards carbonate deposition in a very shallow platform-lagoon that was bounded shoreward by clastic/ooid bars and passed seaward either to stromatoporoid bioconstructions (bioherms and biostromes) or rudist biostromes. The successive elemental sequences show north-eastward progradational geometries. Three phases of platform development are identified: (1) installation of the shallow platform; (2) development of a lagoon bounded by a stromatoporoid barrier and (3) development of an Urgonian-type platform dominated by rudists. During the early Aptian, the Bedmar-Jódar platform was partially isolated from the rest of the Prebetic platform and showed overall progradation towards the NE, in contrast to the general south-eastward progradational trend of the Prebetic platform. Sedimentation was controlled by rift-generated extensional tectonics that resulted in tilting of the platform block, causing the deviation of progradation from the general trends of the Prebetic Platform. In addition, climatic influence is inferred from the presence of siliciclastic sediments derived from weathering of the hinterland, which restricted the carbonate factory.

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Inter-annual variability of land surface fluxes across vineyards: the role of climate, phenology, and irrigation management - N. Bambach; W. Kustas; J. Alfieri; F. Gao; J. Prueger; L. Hipps; L. McKee; S. J. Castro; M. M. Alsina; A. J. McElrone (Irrigation Science, 2022)
Irrigation and other agricultural management practices play a key role in land surface fluxes and their interactions with atmospheric processes. California’s Central Valley agricultural productivity is strongly linked to water availability associated with conveyance infrastructure and groundwater, but greater scrutiny over agricultural water use requires better practices particularly during extended and severe drought conditions. The future of irrigated agriculture in California is expected to be characterized neither by perpetual scarcity nor by widespread abundance. Thus, further advancing irrigation technologies and improving management practices will be key for California’s agriculture sustainability. In this study, we present micrometeorological observations from the Grape Remote Sensing Atmospheric Profile and Evapotranspiration eXperiment (GRAPEX) project. Daily, seasonal, and inter-seasonal surface flux patterns and relationships across five vineyards over three distinct California wine production regions were investigated. Vineyard actual evapotranspiration showed significant differences at the sub-daily and daily scale when comparisons across wine production regions and varieties were performed. Water use in vineyards in the Central Valley was about 70% greater in comparison to the vineyards at the North Coast area due to canopy size, atmospheric demand, and irrigation inputs. Inter-annual variability of surface fluxes was also significant, even though, overall weather conditions (i.e., air temperature, vapor pressure deficit, wind speed, and solar radiation) were not significantly different. Thus, not only irrigation but also other management practices played a key role in seasonal water use, and given these differences, we conclude that further advancing ground-based techniques to quantify crop water use at an operational scale will be key to facing California’s agriculture present and future water challenges.

Evapotranspiration uncertainty at micrometeorological scales: the impact of the eddy covariance energy imbalance and correction methods - N. Bambach; W. Kustas; J. Alfieri; J. Prueger; L. Hipps; L. McKee; S. J. Castro; J. Volk; M. M. Alsina; A. J. McElrone (Irrigation Science, 2022)
Under ideal conditions, evapotranspiration ( ET ) fluxes derived through the eddy covariance (EC) technique are considered a direct measure of actual ET . Eddy covariance flux measurements provide estimates at a temporal frequency that allows examining sub-daily, daily, and seasonal scale processes and relationships between different surface fluxes. The Grape Remote Sensing Atmospheric Profile and Evapotranspiration eXperiment (GRAPEX) project has collected micrometeorological and biophysical data to ground-truth new remote sensing tools for fine-tuning vineyard irrigation management across numerous sites since 2013. This rich dataset allows us to quantify the impact of different approaches to estimate daily ET fluxes, while accounting for energy imbalance. This imbalance results from the lack of agreement between the total available energy and turbulent fluxes derived by the EC technique. We found that different approaches to deal with this energy imbalance can lead to uncertainty in daily ET estimates of up to 50%. Over the growing season, this uncertainty can lead to considerable biases in crop water use estimates, which in some cases were equivalent to ~ 1/3rd of the total growing season applied irrigation We analyzed ET uncertainty relative to atmospheric meteorological, stability, and advective conditions, and highlight the importance of recognizing limitations of micrometeorological observational techniques, considered state of the art, to quantify ET for model validation and field-scale monitoring. This study provides a framework to quantify daily ET estimates’ uncertainty and expected reliability when using the eddy covariance technique for ground-truthing or model validation purposes.

Older adults’ episodic memory is related to a neurophysiological marker of brain cholinergic activity - Patrick S. R. Davidson; Galit Karpov; Lauriane Giguère; Alex W. Castro; François Tremblay (Experimental Brain Research, 2022)

Physicochemical and computational analysis of the melamine resin derivative for the glyphosate absorption from water using Langmuir-type model - L. Morales-Quintana; D. Bustos; J. Gallego; O. Valdes; L. Guzmán; F. M. Nachtigall; A. Marican; E. W. Hernández-Rodríguez; F. Avila-Salas; W. Bueno-Silva; L. S. Santos; R. I. Castro (International Journal of Environmental Science and Technology, 2022)

Genetic diversity of medically important scorpions of the genus Centruroides (Buthidae) from Panama including two endemic species - Samuel Escudero-Sanjur; Edgardo Castro-Perez; Hildaura Acosta De Patiño; Ichwaku Rastogi; Carlos W. Ramos (Journal of Genetics, 2022)

Preparation of Ciguatoxin Reference Materials from Canary Islands (Spain) and Madeira Archipelago (Portugal) Fish - David Castro; Pablo Estévez; José Manuel Leao-Martins; Robert W. Dickey; Natalia García-Álvarez; Fernando Real; Pedro Reis Costa; Ana Gago-Martínez (Journal of Marine Science and Engineering, 2022)
Ciguatoxins (CTXs) are naturally occurring neurotoxins that can accumulate in fish and cause Ciguatera Poisoning (CP) in seafood consumers. Ciguatoxic fish have been detected in tropical and subtropical regions of the world including the Pacific and Indian Oceans, the Caribbean Sea, and more recently in the northeast Atlantic Ocean. The biogeographic distribution of ciguatoxic fish appears to be expanding; however, the paucity of CTX standards and reference materials limits the ability of public health authorities to monitor for these toxins in seafood supply chains. Recent reports establish that Caribbean Ciguatoxin-1 (C-CTX1) is the principal toxin responsible for CP cases and outbreaks in the northeast Atlantic Ocean and that C-CTX congener profiles in contaminated fish samples match those from the Caribbean Sea. Therefore, in this work, C-CTX reference materials were prepared from fish obtained from the northeast Atlantic Ocean. The collection of fish specimens (e.g., amberjack, grouper, or snapper) was screened for CTX-like toxicity using the in vitro sodium channel mouse neuroblastoma cytotoxicity assay (N2a cell assay). Muscle and liver tissues from toxic specimens were pooled for extraction and purified products were ultimately profiled and quantified by comparison with authentic C-CTX1 using LC-MS/MS. This work presents a detailed protocol for the preparation of purified C-CTX reference materials to enable continued research and monitoring of the ciguatera public health hazard. To carry out this work, C-CTX1 was isolated and purified from fish muscle and liver tissues obtained from the Canary Islands (Spain) and Madeira archipelago (Portugal).

Sea Ice and Substratum Shape Extensive Kelp Forests in the Canadian Arctic - Karen Filbee-Dexter; Kathleen A. MacGregor; Camille Lavoie; Ignacio Garrido; Jesica Goldsmit; Laura Castro de la Guardia; Kimberly L. Howland; Ladd E. Johnson; Brenda Konar; Christopher W. McKindsey; Christopher J. Mundy; Robert W. Schlegel; et al. (Frontiers in Marine Science, 2022)
The coastal zone of the Canadian Arctic represents 10% of the world’s coastline and is one of the most rapidly changing marine regions on the planet. To predict the consequences of these environmental changes, a better understanding of how environmental gradients shape coastal habitat structure in this area is required. We quantified the abundance and diversity of canopy forming seaweeds throughout the nearshore zone (5–15 m) of the Eastern Canadian Arctic using diving surveys and benthic collections at 55 sites distributed over 3,000 km of coastline. Kelp forests were found throughout, covering on average 40.4% (±29.9 SD) of the seafloor across all sites and depths, despite thick sea ice and scarce hard substrata in some areas. Total standing macroalgal biomass ranged from 0 to 32 kg m –2 wet weight and averaged 3.7 kg m –2 (±0.6 SD) across all sites and depths. Kelps were less abundant at depths of 5 m compared to 10 or 15 m and distinct regional assemblages were related to sea ice cover, substratum type, and nutrient availability. The most common community configuration was a mixed assemblage of four species: Agarum clathratum (14.9% benthic cover ± 12.0 SD), Saccharina latissima (13% ± 14.7 SD), Alaria esculenta (5.4% ± 1.2 SD), and Laminaria solidungula (3.7% ± 4.9 SD). A. clathratum dominated northernmost regions and S. latissima and L. solidungula occurred at high abundance in regions with more open water days. In southeastern areas along the coast of northern Labrador, the coastal zone was mainly sea urchin barrens, with little vegetation. We found positive relationships between open water days (days without sea ice) and kelp biomass and seaweed diversity, suggesting kelp biomass could increase, and the species composition of kelp forests could shift, as sea ice diminishes in some areas of the Eastern Canadian Arctic. Our findings demonstrate the high potential productivity of this extensive coastal zone and highlight the need to better understand the ecology of this system and the services it provides.

Nanotechnology-Driven Cell-Based Therapies in Regenerative Medicine - D. Alzate-Correa; W. R. Lawrence; A. Salazar-Puerta; N. Higuita-Castro; D. Gallego-Perez (The AAPS Journal, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Ant diversity studies in Brazil: an overview of the myrmecological research in a megadiverse country - F. A. Schmidt; C. R. Ribas; R. M. Feitosa; F. B. Baccaro; A. C. M. de Queiroz; T. G. Sobrinho; Y. Quinet; K. S. Carvalho; T. Izzo; M. S. de Castro Morini; A. Nogueira; H. M. Torezan-Silingardi; et al. (Insectes Sociaux, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Stratification strength and light climate explain variation in chlorophyll a at the continental scale in a European multilake survey in a heatwave summer - Daphne Donis; Evanthia Mantzouki; Daniel F. McGinnis; Dominic Vachon; Irene Gallego; Hans‐Peter Grossart; Lisette N. de Senerpont Domis; Sven Teurlincx; Laura Seelen; Miquel Lürling; Yvon Verstijnen; Valentini Maliaka; et al. (Limnology and Oceanography, 2021)
To determine the drivers of phytoplankton biomass, we collected standardized morphometric, physical, and biological data in 230 lakes across the Mediterranean, Continental, and Boreal climatic zones of the European continent. Multilinear regression models tested on this snapshot of mostly eutrophic lakes (median total phosphorus [TP] = 0.06 and total nitrogen [TN] = 0.7 mg L −1 ), and its subsets (2 depth types and 3 climatic zones), show that light climate and stratification strength were the most significant explanatory variables for chlorophyll a (Chl a ) variance. TN was a significant predictor for phytoplankton biomass for shallow and continental lakes, while TP never appeared as an explanatory variable, suggesting that under high TP, light, which partially controls stratification strength, becomes limiting for phytoplankton development. Mediterranean lakes were the warmest yet most weakly stratified and had significantly less Chl a than Boreal lakes, where the temperature anomaly from the long‐term average, during a summer heatwave was the highest (+4°C) and showed a significant, exponential relationship with stratification strength. This European survey represents a summer snapshot of phytoplankton biomass and its drivers, and lends support that light and stratification metrics, which are both affected by climate change, are better predictors for phytoplankton biomass in nutrient‐rich lakes than nutrient concentrations and surface temperature.

Refining Fisheries Advice With Stock-Specific Ecosystem Information - Jacob W. Bentley; Mathieu G. Lundy; Daniel Howell; Steven E. Beggs; Alida Bundy; Francisco de Castro; Clive J. Fox; Johanna J. Heymans; Christopher P. Lynam; Debbi Pedreschi; Pia Schuchert; Natalia Serpetti; et al. (Frontiers in Marine Science, 2021)
Although frequently suggested as a goal for ecosystem-based fisheries management, incorporating ecosystem information into fisheries stock assessments has proven challenging. The uncertainty of input data, coupled with the structural uncertainty of complex multi-species models, currently makes the use of absolute values from such models contentious for short-term single-species fisheries management advice. Here, we propose a different approach where the standard assessment methodologies can be enhanced using ecosystem model derived information. Using a case study of the Irish Sea, we illustrate how stock-specific ecosystem indicators can be used to set an ecosystem-based fishing mortality reference point (F ECO ) within the “Pretty Good Yield” ranges for fishing mortality which form the present precautionary approach adopted in Europe by the International Council for the Exploration of the Sea (ICES). We propose that this new target, F ECO , can be used to scale fishing mortality down when the ecosystem conditions for the stock are poor and up when conditions are good. This approach provides a streamlined quantitative way of incorporating ecosystem information into catch advice and provides an opportunity to operationalize ecosystem models and empirical indicators, while retaining the integrity of current assessment models and the F MSY -based advice process.

Recent developments combining ensemble smoother and deep generative networks for facies history matching - Smith W. A. Canchumuni; Jose D. B. Castro; Júlia Potratz; Alexandre A. Emerick; Marco Aurélio C. Pacheco (Computational Geosciences, 2021)

Mosaic genome evolution and phylogenetics of Chrysodeixis includens nucleopolyhedrovirus (ChinNPV) and virulence of seven new isolates from the Brazilian states of Minas Gerais and Mato Grosso - Peter W. Inglis; Luis Arthur V. M. Santos; Saluana R. Craveiro; Bergmann M. Ribeiro; Maria Elita B. Castro (Archives of Virology, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Delinted cottonseed in diets for finishing sheep - W. J. R. Castro; A. M. Zanine; D. J. Ferreira; A. L. Souza; R. M. A. Pinho; M. O. M. Parente; H. N. Parente; E. M. Santos (Tropical Animal Health and Production, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Coral reef resilience to thermal stress in the Eastern Tropical Pacific - Mauricio Romero‐Torres; Alberto Acosta; Ana M. Palacio‐Castro; Eric A. Treml; Fernando A. Zapata; David A. Paz‐García; James W. Porter (Global Change Biology, 2020)
Coral reefs worldwide are threatened by thermal stress caused by climate change. Especially devastating periods of coral loss frequently occur during El Niño‐Southern Oscillation (ENSO) events originating in the Eastern Tropical Pacific (ETP). El Niño‐induced thermal stress is considered the primary threat to ETP coral reefs. An increase in the frequency and intensity of ENSO events predicted in the coming decades threatens a pan‐tropical collapse of coral reefs. During the 1982–1983 El Niño, most reefs in the Galapagos Islands collapsed, and many more in the region were decimated by massive coral bleaching and mortality. However, after repeated thermal stress disturbances, such as those caused by the 1997–1998 El Niño, ETP corals reefs have demonstrated regional persistence and resiliency. Using a 44 year dataset (1970–2014) of live coral cover from the ETP, we assess whether ETP reefs exhibit the same decline as seen globally for other reefs. Also, we compare the ETP live coral cover rate of change with data from the maximum Degree Heating Weeks experienced by these reefs to assess the role of thermal stress on coral reef survival. We find that during the period 1970–2014, ETP coral cover exhibited temporary reductions following major ENSO events, but no overall decline. Further, we find that ETP reef recovery patterns allow coral to persist under these El Niño‐stressed conditions, often recovering from these events in 10–15 years. Accumulative heat stress explains 31% of the overall annual rate of change of living coral cover in the ETP. This suggests that ETP coral reefs have adapted to thermal extremes to date, and may have the ability to adapt to near‐term future climate‐change thermal anomalies. These findings for ETP reef resilience may provide general insights for the future of coral reef survival and recovery elsewhere under intensifying El Niño scenarios.

Nitrogen flux into metabolites and microcystins changes in response to different nitrogen sources in Microcystis aeruginosa NIES ‐843 - Lauren E. Krausfeldt; Abigail T. Farmer; Hector F. Castro; Gregory L. Boyer; Shawn R. Campagna; Steven W. Wilhelm (Environmental Microbiology, 2020)
Summary The over‐enrichment of nitrogen (N) in the environment has contributed to severe and recurring harmful cyanobacterial blooms, especially by the non‐N 2 ‐fixing Microcystis spp. N chemical speciation influences cyanobacterial growth, persistence and the production of the hepatotoxin microcystin, but the physiological mechanisms to explain these observations remain unresolved. Stable‐labelled isotopes and metabolomics were employed to address the influence of nitrate, ammonium, and urea on cellular physiology and production of microcystins in Microcystis aeruginosa NIES‐843. Global metabolic changes were driven by both N speciation and diel cycling. Tracing 15 N‐labelled nitrate, ammonium, and urea through the metabolome revealed N uptake, regardless of species, was linked to C assimilation. The production of amino acids, like arginine, and other N‐rich compounds corresponded with greater turnover of microcystins in cells grown on urea compared to nitrate and ammonium. However, 15 N was incorporated into microcystins from all N sources. The differences in N flux were attributed to the energetic efficiency of growth on each N source. While N in general plays an important role in sustaining biomass, these data show that N‐speciation induces physiological changes that culminate in differences in global metabolism, cellular microcystin quotas and congener composition.

Role of VEGFs in metabolic disorders - M. di Somma; M. Vliora; E. Grillo; B. Castro; E. Dakou; W. Schaafsma; J. Vanparijs; M. Corsini; C. Ravelli; E. Sakellariou; S. Mitola (Angiogenesis, 2020)

Removal of Zn and Cd from Overlying Water by Mangrove Sediments: Testing the Effects of Sediment Resuspension/Redeposition Events - K. N. Suzuki; R. J. M. Castro; M. N. Sondermann; E. C. Machado; A. B. Bellido; R. T. Lopes; W. Machado (Water, Air, & Soil Pollution, 2020)

The Impact of the Right Coronary Artery Geometric Parameters on Hemodynamic Performance - N. Pinho; L. C. Sousa; C. F. Castro; C. C. António; M. Carvalho; W. Ferreira; R. Ladeiras-Lopes; N. D. Ferreira; P. Braga; N. Bettencourt; S. I. S. Pinto (Cardiovascular Engineering and Technology, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Enzyme-linked immunosorbent assay and agar gel immunodiffusion assay for diagnosis of equine infectious anemia employing p26 protein fused to the maltose-binding protein - Karin F. L. P. Fontes; Luiz C. Silva-Júnior; Sérgio A. Nascimento; Daniel P. Chaves; Jose W. Pinheiro-Júnior; Antonio C. Freitas; Roberto S. Castro; André L. S. Jesus (Archives of Virology, 2018)

Prospects of Cannabidiol for Easing Status Epilepticus-Induced Epileptogenesis and Related Comorbidities - Dinesh Upadhya; Olagide W. Castro; Raghavendra Upadhya; Ashok K. Shetty (Molecular Neurobiology, 2018)

Low salinity as a biosecurity tool for minimizing biofouling on ship sea chests - Maria Cecilia T. de Castro; Thomas Vance; Anna L. E. Yunnie; Timothy W. Fileman; Jason M. Hall-Spencer (Ocean Science, 2018)
Biofouling is a major vector in the transfer of non-native species around the world. Species can be transported on virtually all submerged areas of ships (e.g. hulls, sea chests, propellers) and so antifouling systems are used to reduce fouling. However, with increased regulation of biocides used in antifoulants (e.g. the International Maritime Organization tributyltin ban in 2008), there is a need to find efficient and sustainable alternatives. Here, we tested the hypothesis that short doses of low salinity water could be used to kill fouling species in sea chests. Settlement panels were suspended at 1.5 m depth in a Plymouth marina for 24 months by which time they had developed mature biofouling assemblages. We exposed these panels to three different salinities (7, 20 and 33) for 2 hours using a model sea chest placed in the marina and flushed with freshwater. Fouling organism diversity and abundance were assessed before panels were treated, immediately after treatment, and then 1 week and 1 month later. Some native ascidian Dendrodoa grossularia survived, but all other macrobenthos were killed by the salinity 7 treatment after 1 week. The salinity 20 treatment was not effective at killing the majority of fouling organisms. On the basis of these results, we propose that sea chests be flushed with freshwater for at least 2 hours before ships leave port. This would not cause unnecessary delays or costs and could be a major step forward in improving biosecurity.

Screening for germline mutations in mismatch repair genes in patients with Lynch syndrome by next generation sequencing - Barbara Luísa Soares; Ayslan Castro Brant; Renan Gomes; Tatiane Pastor; Naye Balzan Schneider; Ândrea Ribeiro-dos-Santos; Paulo Pimentel de Assumpção; Maria Isabel W. Achatz; Patrícia Ashton-Prolla; Miguel Angelo Martins Moreira (Familial Cancer, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Source Functions and Path Effects from Earthquakes in the Farallon Transform Fault Region, Gulf of California, Mexico that Occurred on October 2013 - Raúl R. Castro; Joann M. Stock; Egill Hauksson; Robert W. Clayton (Pure and Applied Geophysics, 2017)

RA Differentiation Enhances Dopaminergic Features, Changes Redox Parameters, and Increases Dopamine Transporter Dependency in 6-Hydroxydopamine-Induced Neurotoxicity in SH-SY5Y Cells - Fernanda M. Lopes; Leonardo Lisbôa da Motta; Marco A. De Bastiani; Bianca Pfaffenseller; Bianca W. Aguiar; Luiz F. de Souza; Geancarlo Zanatta; Daiani M. Vargas; Patrícia Schönhofen; Giovana F. Londero; Liana M. de Medeiros; Valder N. Freire; et al. (Neurotoxicity Research, 2017)

Identification and genetic characterization of classical swine fever virus isolates in Brazil: a new subgenotype - Marta N. F. Silva; Diogo M. F. Silva; Adriana S. Leite; Ana L. V. Gomes; Antonio C. Freitas; Jose W. Pinheiro-Junior; Roberto S. Castro; Andre L. S. Jesus (Archives of Virology, 2017)

Quantitative structure-toxicity relationships and molecular highlights about Aedes aegypti larvicidal activity of monoterpenes and related compounds - Edilson B. Alencar Filho; Joseph W. Castro Silva; Sócrates C.H. Cavalcanti (Medicinal Chemistry Research, 2016)

Event-related fields evoked by vocal response inhibition: a comparison of younger and older adults - Leidy J. Castro-Meneses; Blake W. Johnson; Paul F. Sowman (Experimental Brain Research, 2016)

Efficacy of Cinnamaldehyde Against Enteric Viruses and Its Activity After Incorporation Into Biodegradable Multilayer Systems of Interest in Food Packaging - M. J. Fabra; J. L. Castro-Mayorga; W. Randazzo; J. M. Lagarón; A. López-Rubio; R. Aznar; G. Sánchez (Food and Environmental Virology, 2016)

Vocal response inhibition is enhanced by anodal tDCS over the right prefrontal cortex - Leidy J. Castro-Meneses; Blake W. Johnson; Paul F. Sowman (Experimental Brain Research, 2016)

Trophoblast expression dynamics of the tumor suppressor gene gastrokine 2 - Fabian B. Fahlbusch; Matthias Ruebner; Hanna Huebner; Gudrun Volkert; Hannah Bartunik; Ilona Winterfeld; Andrea Hartner; Carlos Menendez-Castro; Stephanie C. Noegel; Ines Marek; David Wachter; Regine Schneider-Stock; et al. (Histochemistry and Cell Biology, 2015)

Detection of a new QTL/gene for growth habit in chickpea CaLG1 using wide and narrow crosses - L. Ali; S. Azam; J. Rubio; H. Kudapa; E. Madrid; R. K. Varshney; P. Castro; W. Chen; J. Gil; T. Millan (Euphytica, 2015)

Lessons for resource conservation from two contrasting small-scale fisheries - Hampus Eriksson; Maricela de la Torre-Castro; Steven W. Purcell; Per Olsson (Ambio, 2015)

Fresh and vitrified bovine preantral follicles have different nutritional requirements during in vitro culture - S. V. Castro; A. A. Carvalho; C. M. G. Silva; F. W. Santos; C. C. Campello; J. R. Figueiredo; A. P. R. Rodrigues (Cell and Tissue Banking, 2014)

Kinetics and regulation of lactose transport and metabolism in Kluyveromyces lactis JA6 - A. M. Santos; W. B. Silveira; L. G. Fietto; R. L. Brandão; I. M. Castro (World Journal of Microbiology and Biotechnology, 2014)

Basin‐scale phenology and effects of climate variability on global timing of initial seaward migration of Atlantic salmon ( Salmo salar ) - Jaime Otero; Jan Henning L'Abée‐Lund; Ted Castro‐Santos; Kjell Leonardsson; Geir O. Storvik; Bror Jonsson; Brian Dempson; Ian C. Russell; Arne J. Jensen; Jean‐Luc Baglinière; Mélanie Dionne; John D. Armstrong; et al. (Global Change Biology, 2014)
Migrations between different habitats are key events in the lives of many organisms. Such movements involve annually recurring travel over long distances usually triggered by seasonal changes in the environment. Often, the migration is associated with travel to or from reproduction areas to regions of growth. Young anadromous Atlantic salmon ( Salmo salar ) emigrate from freshwater nursery areas during spring and early summer to feed and grow in the North Atlantic Ocean. The transition from the freshwater (‘parr’) stage to the migratory stage where they descend streams and enter salt water (‘smolt’) is characterized by morphological, physiological and behavioural changes where the timing of this parr‐smolt transition is cued by photoperiod and water temperature. Environmental conditions in the freshwater habitat control the downstream migration and contribute to within‐ and among‐river variation in migratory timing. Moreover, the timing of the freshwater emigration has likely evolved to meet environmental conditions in the ocean as these affect growth and survival of the post‐smolts. Using generalized additive mixed‐effects modelling, we analysed spatio‐temporal variations in the dates of downstream smolt migration in 67 rivers throughout the North Atlantic during the last five decades and found that migrations were earlier in populations in the east than the west. After accounting for this spatial effect, the initiation of the downstream migration among rivers was positively associated with freshwater temperatures, up to about 10 °C and levelling off at higher values, and with sea‐surface temperatures. Earlier migration occurred when river discharge levels were low but increasing. On average, the initiation of the smolt seaward migration has occurred 2.5 days earlier per decade throughout the basin of the North Atlantic. This shift in phenology matches changes in air, river, and ocean temperatures, suggesting that Atlantic salmon emigration is responding to the current global climate changes.

Allele-specific amplification for the detection of ascochyta blight resistance in chickpea - E. Madrid; W. Chen; P. N. Rajesh; P. Castro; T. Millán; J. Gil (Euphytica, 2013)

Can the red palm mite threaten the Amazon vegetation? - Manoel G. C. Gondim; Tatiane M. M. G. Castro; Alberto L. Marsaro; Denise Navia; José W. S. Melo; Peterson R. Demite; Gilberto J. de Moraes (Systematics and Biodiversity, 2012)

Identification and sequence analysis of the Condylorrhiza vestigialis MNPV p74 gene - Maria Elita B. Castro; Débora P. Paula; Geraldo F. Almeida; Zilda Maria A. Ribeiro; Marlinda L. Souza; Peter W. Inglis; Bergmann M. Ribeiro (Virus Genes, 2011)

Letter to the Editor in Chief: Rebuttal to the Letter to the Editor in Chief by Jörg Rinklebe, Rainer Wennrich, Sibylle Mothes Concerning the Article “A Simple and Accurate Method to Measure Total Gaseous Mercury Concentrations in Unsaturated Soils” by Moore et al., DOI:10.1007/s11270-010-0691-7 - Christopher W. Moore; Mark S. Castro; Steven B. Brooks (Water, Air, & Soil Pollution, 2011)

Erratum to: A Simple and Accurate Method to Measure Total Gaseous Mercury Concentrations in Unsaturated Soils - Christopher W. Moore; Mark S. Castro; Steven B. Brooks (Water, Air, & Soil Pollution, 2011)

A Simple and Accurate Method to Measure Total Gaseous Mercury Concentrations in Unsaturated Soils - Christopher. W. Moore; Mark S. Castro; Steven B. Brooks (Water, Air, & Soil Pollution, 2011)

Relationship Between pH and Stream Water Total Mercury Concentrations in Shenandoah National Park - C. W. Moore; B. J. Cosby; J. N. Galloway; M. S. Castro (Water, Air, & Soil Pollution, 2009)

A new species of Muiaria from South America - M. Leonardi; A. Carolina Proaño Castro; W. Rossi (Plant Biosystems, 2009)

Mapping quantitative trait loci for growth responses to exogenously applied stress induced hormones in wheat - A. M. Castro; M. S. Tacaliti; D. Giménez; E. Tocho; O. Dobrovolskaya; A. Vasicek; M. Collado; J. W. Snape; A. Börner (Euphytica, 2008)

A Fluorescent and Phosphorescent Nanoporous Solid: Crystalline Calix[4]arene - Issam Oueslati; Anthony W. Coleman; Baltazar de Castro; Mário N. Berberan-Santos (Journal of Fluorescence, 2008)

Cytological mechanisms of 2n pollen formation in the wild potato Solanum okadae and pollen-pistil relations with the cultivated potato, Solanum tuberosum - Elsa Lucila Camadro; Sandra Karina Saffarano; Juan Carlos Espinillo; Mateo Castro; Phillip W. Simon (Genetic Resources and Crop Evolution, 2008)

Boosting for real and functional samples: an application to an environmental problem - B. M. Fernández de Castro; W. González Manteiga (Stochastic Environmental Research and Risk Assessment, 2008)

Population genetic structure of Earth's largest fish, the whale shark ( Rhincodon typus ) - A. L. F. CASTRO; B. S. STEWART; S. G. WILSON; R. E. HUETER; M. G. MEEKAN; P. J. MOTTA; B. W. BOWEN; S. A. KARL (Molecular Ecology, 2007)
Large pelagic vertebrates pose special conservation challenges because their movements generally exceed the boundaries of any single jurisdiction. To assess the population structure of whale sharks ( Rhincodon typus ), we sequenced complete mitochondrial DNA control regions from individuals collected across a global distribution. We observed 51 single site polymorphisms and 8 regions with indels comprising 44 haplotypes in 70 individuals, with high haplotype ( h = 0.974 ± 0.008) and nucleotide diversity (π = 0.011 ± 0.006). The control region has the largest length variation yet reported for an elasmobranch (1143–1332 bp). Phylogenetic analyses reveal no geographical clustering of lineages and the most common haplotype was distributed globally. The absence of population structure across the Indian and Pacific basins indicates that oceanic expanses and land barriers in Southeast Asia are not impediments to whale shark dispersal. We did, however, find significant haplotype frequency differences (amova, F ST = 0.107, P

Assessment of the spread of chestnut ink disease using remote sensing and geostatistical methods - L. Martins; J. Castro; W. Macedo; C. Marques; C. Abreu (European Journal of Plant Pathology, 2007)

Metal Content of the Gulf of California Blue Shrimp Litopenaeus stylirostris (Stimpson) - M. G. Frías-Espericueta; G. Izaguirre-Fierro; F. Valenzuela-Quiñonez; J. I. Osuna-López; D. Voltolina; G. López-López; M. D. Muy-Rangel; W. Rubio-Castro (Bulletin of Environmental Contamination and Toxicology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Marine extinctions revisited - Pablo del Monte‐Luna; Daniel Lluch‐Belda; Elisa Serviere‐Zaragoza; Roberto Carmona; Héctor Reyes‐Bonilla; David Aurioles‐Gamboa; José Luis Castro‐Aguirre; Sergio A. Guzmán del Próo; Oscar Trujillo‐Millán; Barry W. Brook (Fish and Fisheries, 2007)
In recent years, more than 130 extinctions have been estimated to have occurred in the marine realm. Here we review this body of evidence and show that this figure may actually be overestimated by as much as 50%. We argue that previous estimates have not fully taken into account critical uncertainties such as naturally variable geographical distributions, and have misinterpreted documentary evidence. However, current evidence indicates that some sharks, rays and reef‐associated species, although not necessarily geographically restricted, are particularly vulnerable to anthropogenic impacts and now occur in very low numbers. Overestimating extinctions is of concern because it could reduce confidence in the credibility of the ‘extinct’ category in threatened species lists and, ultimately, be used to question the integrity of conservation and management policies. We suggest that when integrating future checklists of marine extinct species, there needs to be a more rigorous use of the terminology of extinction, and participation by specialists in each of the particular taxonomic groups involved.

Sensitivity studies of the RegCM3 simulation of summer precipitation, temperature and local wind field in the Caribbean Region - D. Martínez-Castro; R. Porfirio da Rocha; A. Bezanilla-Morlot; L. Alvarez-Escudero; J. P. Reyes-Fernández; Y. Silva-Vidal; R. W. Arritt (Theoretical and Applied Climatology, 2006)

Intracellular S-adenosylhomocysteine increased levels are associated with DNA hypomethylation in HUVEC - Rita Castro; Isabel Rivera; Carla Martins; Eduard A. Struys; Erwin E. W. Jansen; Nuno Clode; Luís M. Graça; Henk J. Blom; Cornelis Jakobs; Isabel Tavares de Almeida (Journal of Molecular Medicine, 2005)

Stable isotope probing analysis of the influence of liming on root exudate utilization by soil microorganisms - J. Ignacio Rangel‐Castro; Ken Killham; Nick Ostle; Graeme W. Nicol; Ian C. Anderson; Charlie M. Scrimgeour; Phil Ineson; Andy Meharg; Jim I. Prosser (Environmental Microbiology, 2005)
Summary Rhizosphere microorganisms play an important role in soil carbon flow, through turnover of root exudates, but there is little information on which organisms are actively involved or on the influence of environmental conditions on active communities. In this study, a 13 CO 2 pulse labelling field experiment was performed in an upland grassland soil, followed by RNA‐stable isotope probing (SIP) analysis, to determine the effect of liming on the structure of the rhizosphere microbial community metabolizing root exudates. The lower limit of detection for SIP was determined in soil samples inoculated with a range of concentrations of 13 C‐labelled Pseudomonas fluorescens and was found to lie between 10 5 and 10 6 cells per gram of soil. The technique was capable of detecting microbial communities actively assimilating root exudates derived from recent photo‐assimilate in the field. Denaturing gradient gel electrophoresis (DGGE) profiles of bacteria, archaea and fungi derived from fractions obtained from caesium trifluoroacetate (CsTFA) density gradient ultracentrifugation indicated that active communities in limed soils were more complex than those in unlimed soils and were more active in utilization of recently exuded 13 C compounds. In limed soils, the majority of the community detected by standard RNA‐DGGE analysis appeared to be utilizing root exudates. In unlimed soils, DGGE profiles from 12 C and 13 C RNA fractions differed, suggesting that a proportion of the active community was utilizing other sources of organic carbon. These differences may reflect differences in the amount of root exudation under the different conditions.

An antecedent of the MHC-linked genomic region in amphioxus - L. Filipe C. Castro; Rebecca F. Furlong; Peter W. H. Holland (Immunogenetics, 2004)

Input-Output Budgets of Inorganic Nitrogen for 24 Forest Watersheds in the Northeastern United States: A Review - John L. Campbell; James W. Hornbeck; Myron J. Mitchell; Mary Beth Adams; Mark S. Castro; Charles T. Driscoll; Jeffrey S. Kahl; James N. Kochenderfer; Gene E. Likens; James A. Lynch; Peter S. Murdoch; Sarah J. Nelson; et al. (Water, Air, & Soil Pollution, 2004)

Nesting characteristics of the olive ridley turtle ( Lepidochelys olivacea ) in Cabo Pulmo, southern Baja California - M. C. Lpez-Castro; R. Carmona; W. J. Nichols (Marine Biology, 2003)

Effects of Disturbance on Nitrogen Export from Forested Lands of the Chesapeake Bay Watershed - Keith N. Eshleman; Robert H. Gardner; Steven W. Seagle; Nancy M. Castro; Daniel A. Fiscus; James R. Webb; James N. Galloway; Frank A. Deviney; Alan T. Herlihy (Environmental Monitoring and Assessment, 2000)

On the prosthetic groups of the NiFe sulfhydrogenase from Pyrococcus furiosus: topology, structure, and temperature-dependent redox chemistry - Pedro J. Silva; Baltazar de Castro; W. R. Hagen (JBIC Journal of Biological Inorganic Chemistry, 1999)

Frozen cultured sheets of human epidermal keratinocytes enhance healing of full-thickness wounds in mice - Elisa Tamariz; Meytha Marsch-Moreno; Federico Castro-Muñozledo; Victor Tsutsumi; W. Kuri-Harcuch (Cell and Tissue Research, 1999)

β-Tubulin accumulation and DNA synthesis are sequentially resumed in embryo organs of cucumber (Cucumis sativus L.) seeds during germination - Hai -Chun Jing; André A. M. van Lammeren; Renato D. de Castro; Raoul J. Bino; Henk W. M. Hilhorst; Steven P. C. Groot (Protoplasma, 1999)

Follow-up of mercury levels in fish, human hair and urine in the Madeira and Tapajós basins, Amazon, Brazil - O. Malm; J. R. D. Guimarães; M. B. Castro; W. R. Bastos; J. P. Viana; F. J. P. Branches; E. G. Silveira; W. C. Pfeiffer (Water, Air, & Soil Pollution, 1997)

African swine fever virus - R. C. Wardley; C. de M. Andrade; D. N. Black; F. L. de Castro Portugal; L. Enjuanes; W. R. Hess; C. Mebus; A. Ordas; D. Rutili; J. Sanchez Vizcaino; J. D. Vigario; P. J. Wilkinson; et al. (Archives of Virology, 1983)

Metabolism of acetaldehyde and Custers effect in the yeast - J. M. Carrascosa; Mara Dolores Viguera; I. Nez de Castro; W. A. Scheffers (Antonie van Leeuwenhoek, 1981)